2020
DOI: 10.3390/app10228030
|View full text |Cite
|
Sign up to set email alerts
|

Limited Power Point Tracking for a Small-Scale Wind Turbine Intended to Be Integrated in a DC Microgrid

Abstract: Limited power point tracking (LPPT) is emerging as a new technology for power management controllers for small-scale wind turbines (SSWTs) thanks to its advantages in terms of operation flexibility, economy and system security. LPPT operates in such a way that power requested by the user can be extracted from the wind turbine while respecting constraints. However, operating in LPPT mode still requires a deep understanding to obtain a compromise between minimizing power oscillations and transient response. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…The angle between voltage and current of stationary load should be stable. Grid-connected systems of photovoltaic, direct drive fan and other new energy sources, as well as flexible DC power transmission can be regarded as converter grid-connected models, which have multi-time scale characteristics, and their instability phenomenon shows broad frequency characteristics [23][24][25] . The main criteria for taking phase locked loop as the leading link www.nature.com/scientificreports/ include: stability criteria for extracting the main loop of phase locked loop; Generalized impedance criterion of phase angle impedance is extracted.…”
Section: Analysis Methods Of Voltage and Current Angle And Impedance ...mentioning
confidence: 99%
“…The angle between voltage and current of stationary load should be stable. Grid-connected systems of photovoltaic, direct drive fan and other new energy sources, as well as flexible DC power transmission can be regarded as converter grid-connected models, which have multi-time scale characteristics, and their instability phenomenon shows broad frequency characteristics [23][24][25] . The main criteria for taking phase locked loop as the leading link www.nature.com/scientificreports/ include: stability criteria for extracting the main loop of phase locked loop; Generalized impedance criterion of phase angle impedance is extracted.…”
Section: Analysis Methods Of Voltage and Current Angle And Impedance ...mentioning
confidence: 99%
“…Another case where experiments were involved in a PV system showed that conventional P&O techniques are very sensitive to step size (which is related to the disadvantages of this method) [51]. Despite the fact that P&O is one of the most popular MPPT algorithm in industry due to its simplicity [54,55]. Regardless of these assets, the major downsides are high chattering when the MPP is reached and the lack of success to achieve this point [56].…”
Section: Perturb and Observationmentioning
confidence: 99%
“…Up to now, three main MPPT control schemes for wind energy conversion systems (WECS) have been developed including hill-climb search (HCS) method [5][6][7][8][9][10], tip speed ratio (TSR) method [11][12][13], and power signal feedback (PSF) method [14,15]. In the HCS control method, based on the locality of the operating point, the maximum power point of the wind-generator is continuously searched.…”
Section: Introductionmentioning
confidence: 99%